Peran Korban Kausa Kejahatan Cyber Sexual Harrasement di Media Sosial Dalam Kajian Viktimologi : Kajian Viktimologi dalam mengetahui seberapa jauh peran korban dalam kejahatan Cyber Sexual Harrasement - kadek, wiwin asita (VYAVAHARA DUTA, 2025)
The crime of Cyber Sexual Harrasment is a crime that is not only responsible for the actions of the perpetrator as one of the causes of this crime on social media, but the role of the victim can also affect the occurrence of this crime seen for how the context of posting photos/videos that are presented to the public. Through the study of victimology, which studies about victims, the author can find out what theories affect the emergence of crime caused by the role of victims. The purpose of writing this article is 1). To find out what causes the crime of Cyber Sexual Harrasement committed by the perpetrator to the victim of social media users who are not even known, 2). How much the role of the victim influences the intention of the perpetrator to commit the crime of Cyber Sexual Harrasement in general on social media, and 3). How is the regulation related to the crime of cyber sexual harassment in cyberspace. The author conducts qualitative research using a descriptive method which aims to collect data and explain how a phenomenon occurs and clearly describes the findings and connects several theories of victimology as a study of the occurrence of the phenomenon. Through the study of Viktimology, the answers to the objectives of this research can be explained in detail and systematically so as to provide a deep understanding for the reader.